The Bandkeramik settlement of Vaihingen an der Enz, Kreis Ludwigsburg (Baden-Württemberg): an integrated perspective on land use, economy and diet - Bogaard, A; Arbogast, R-M; Ebersbach, R; Fraser, RA; Knipper, C; Krahn, C; Schäfer, M; Styring, A; Krause, R (Römisch-Germanische Kommission des Deutschen Archäologischen Instituts, 2017)
In this paper we develop an integrated perspective on land use, economy and diet at the LBK site Vaihingen an der Enz, an extensively excavated settlement and cemetery of the early Neolithic (later 6th millennium cal BC). We synthesise the results of primary and stable isotope analysis of fauna, humans and botanical remains, interpreted in light of material culture variation across the settlement and through the occupation sequence. Our integrated approach reveals a dynamic relationhip between the changing scale and social geography of the community, on the one hand, and land use, on the other.